(untitled) (Estudios Humanísticos. Filología, 1993)
La enseñanza de la pronunciacion francesa en el contexto de los estudiantes españoles exige un acercamiento "metodológico fundamentado en: 1) Conocimiento y utilización de los componentes fonéticos comunes a las dos lenguas; 2) Explotación pedagógica basada en las oposiciones esenciales de la fonética francesa; 3) Estrategias de corrección fonética "verbo-tonales". Estudio de los fonemas franceses de difícil pronunciación para los estudiantes españoles, y propuesta de ejercicios fonéticos. The Teaching of French pronunciation to Spanish students demands a methodological approach based on: 1) te knowledge and usage of the phonetic components common to both languages ; 2) pedagogical exploitation based on the basic oppositions of French phonetics; 3) strategies for the assessment of pnonetic articulation ("méthode verbo-tonale") Study of French phonemes which pose special difficulties for Spanish students and proposal of phonetic exercises.